Measurement of Retinal Vessels as a Biomarker of Cerebrovascular Aging in Older HIV-Positive Men Compared With Controls. (1st February 2018) - Haddow, Lewis; Laverick, Rosanna; Leung, Irene; Post, Frank; Vera, Jaime; Gilson, Richard; Williams, Ian; Boffito, Marta; Sabin, Caroline; Winston, Alan; Peto, Tunde
Abstract : Background: To compare retinal vascular measurements, biomarkers of cerebral small vessel disease, in HIV-positive men aged 50 years and older with similarly aged HIV-negative men and younger HIV-positive men. Methods: We recruited white, nondiabetic men into a cross-sectional substudy of a larger cohort including 3 demographically matched groups. Optic disc–centered 45-degree color fundus photographs were used to calculate central retinal arterial and venous caliber and the arterial–venous ratio (AVR). We used univariate and multivariable linear regression to compare retinal vessel measurements in the 3 groups and to identify factors associated with AVR. Results: All HIV-positive men were virologically suppressed. In a multivariable model, study group was not associated with AVR [adjusted β 0.010 for HIV-positive men <50 (n = 39) compared with HIV-positive men aged ≥50 years (n = 120), 95% confidence interval [CI] −0.018 to 0.038, P = 0.47; adjusted β 0.00002 for HIV-negative men ≥50 years (n = 52), 95% CI −0.022 to 0.022, P = 0.99]. Factors associated with lower AVR were systolic blood pressure (adjusted β −0.009 per +10 mm Hg, 95% CI −0.015 to −0.003, P = 0.002), history of stroke or transient ischemic attack (adjusted β −0.070, 95% CI −0.12 to −0.015, P = 0.01), and recent recreational drug use (adjusted β −0.037, 95% CI −0.057 to −0.018, P = 0.0002). Conclusions: There were no differences in retinal vascular indices between HIV-positive men aged ≥50 years and HIV-negative men aged ≥50 years or HIV-positive men aged <50 years, suggesting that HIV is not associated with an increased burden of cerebral small vessel disease.